Hajatan, Hiburan, dan Konsumsi Minuman Keras: Analisis atas Pergeseran Nilai Sosial-Islam di Masyarakat Pedesaan - Miswadi Miswadi; Dian Tias Aorta (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
The phenomenon of celebrations in rural communities is currently experiencing a significant cultural shift, marked by the dominance of modern entertainment and the rise of alcohol consumption. This phenomenon indicates a degradation of socio-Islamic values ​​and a weakening of social control based on religious and customary norms. This study aims to analyze the transformation of socio-Islamic values ​​in the practice of celebrations accompanied by entertainment and alcohol consumption in rural environments. Using a qualitative approach using a case study method, data were collected through in-depth interviews, participant observation, and documentation studies. Data analysis was conducted thematically using the interactive model of Miles, Huberman, and Saldaña, which includes stages of condensation, data presentation, and verification of conclusions. The results reveal that the meaning of celebrations has shifted from a socio-religious ritual to an arena for displaying social status and mere entertainment. The practice of alcohol consumption has begun to normalize, particularly among young people, driven by the tide of modernization, pressures of social prestige, and the waning authority of religious and traditional leaders. This study concludes that celebrations have become a space for contestation between tradition, Islamic values, and modernity, impacting fundamentally the social structure of rural communities.